DEPOSITORY INSTITUTIONS AND SUSTAINABLE AGRICULTURE IN NIGERIA - Oseghale, Ihayere; Joseph, Ugege; Prince, Abu (International Journal of Research -GRANTHAALAYAH, 2020)
Aligning with Goal two of Sustainable Development Goals (SDGs2) to accomplish zero hunger by the year 2030. This research dives deeper into how Agriculture can be sustained to actualize SDGs2 through the assistance of depository Institutions. The results show that deposit money bank loans, deposit money bank loans rate, exchange rate, government expenditure and agricultural credit sector fund have pose positive effect on agricultural output, only the duo of exchange rate and agricultural credit sector fund indicate a significant impact on agricultural output at the 5% level of significance while deposit money bank loans have a slightly positive significant effect on agricultural output at approximately 10% level of significance. This implies that across the period under investigation, deposit money bank loans, exchange rate and agricultural sector credit fund impose significant and positive contribution to agricultural output.